PENGEBORAN LEPAS PANTAI - Utomo, Budi (Gema Teknologi, 2011)
Budi Utomo, in this paper explain that offshore drilling carried out to obtain crude oil through the oil wells. The means that must exist in the operation of offshore drilling is a bridge structure (plate form) as a place to put the drilling equipment. Known two kinds of platforms, that is platforms permanent (fixed) which stands on the feet of reinforced concrete, and the bridge is not fixed like swamp barges, drilling ship (floaters) and jack-up rig. Jack up rig is one of the offshore rigs that have the ability to elevation in accordance with a sea depth of drilling. Drilling equipment is a range of equipment that is prepared in such a way, so that such a drill rod, and all this equipment has a hole inside that allows for fluid or mud circulation. Â  Key word: Drilling equipment